Assisted Living Reimagined; A reorganizational study of housing for seniors - Bergqvist, Joel (My University, 2026)
As many other countries, Sweden is facing an aging population. Not only will this lead to a need for more people to work in elderly care, it will also lead to a need for more suitable housing options for elderly in need of some kind of care. Today, care provided in the home is the most common solution for elders in need of some kind of support. However, bad accessibility, difficulties moving and isolation often becomes a problem as one grows older. Today the most common option when the need for care becomes unmanageable in the home is a move into an assisted living facility. This is often a dreaded option put off to the last possible moment, making what will most probably be one’s last move to be a stressful and unenjoyable experience. Most assisted living facilities of today are designed by the same principles, with 10 small apartments organized around a shared living space with kitchen, dining and living room. While this may suit some people, for others this organisation is so associated with an institution so that what will probably be their last apartment never truly becomes their home. In this thesis, an alternative to the traditional assisted living facility is explored, where apartments are more generously sized to accommodate a more varied group of elders, while still offering working staff and residents the support needed to allow for extensive care in the home. This not only allows residents to age in place, removing the need for an exhausting move towards one’s latter days, but also gives seniors a place for community and support as they age, making one’s last home something to enjoy and thrive in. The project is applied in eastern Gothenburg, but the ideas and organisational principle can very well be adapted to other sites as well, creating alternatives of living for the ageing population wherever the need may be. With drawings, diagrams and visualizations, this thesis hopes to inspire towards a more varied residential supply for seniors, where one has the right to choose how one lives even as one grows older.
Keywords: HOUSING FOR SENIORS, NURSING HOME, ASSISTED LIVING FACILITY, ELDERLY